Perceived discrimination, collective self-esteem, social support, lucos of control, and well being of MNLF Integrees.[article]. - Redoble-buot, Nerissa G.
This study described the psychological experiences of Moro National Liberation Front(MILF) integrees within the armed forces of the Philippines. The study explored the relationship of perceived discrimination and integrees' well-being. The research also determined if collective self-esteem, social support, and lucos of control are potential mediators in the discrimination-well- being relationship. Finally, ethnic density was also considered if it is affected their well-being. There were 98 porposively sapled Muslim integrees who answered questionnaires. Results showed that discrimination is associated with well-being. Collective self-esteem and social support are mediators in the discrimination-well-being relationship. Lastly, data revealed that the integrees' well-being is alos linked with the ethnic density of their location. Contrary to prediction, results show that Muslim integrees in a prediminantly christian community achieved higher levels of well-being.